Measuring service quality in the Pulau Tinggi and Pulau Sibu Marine Park Area (MPA): visitor's perspective - Hamzah, Nur Amalina; Kamarulzaman, Nitty Hirawaty; Abd. Latif, Ismail; Md. Yusoff, Fatimah (Institut Kajian Dasar Pertanian dan Makanan, Universiti Putra Malaysia, 2015)
The Marine Park Area (MPA) in Malaysia is an attractive place to visit especially for the international visitors who seek for the natural beauty on the island. Due to the richness of coral species, the MPA was established in Malaysia since 1994 to protect these natural heritages and conserve the marine ecosystem. The number of visitors of MPA in Malaysia has increased for the last 12 years, from 10.22 million to 25.03 million between year 2000 and 2012. The overwhelming number of visitors visiting the MPA requires the management of MPA to increase the quality of services and facilities to meet the high expectation from the visitors. This study was aimed at measuring the level of visitor’s satisfaction on service quality at the Pulau Tinggi and Pulau Sibu Marine Park Area located in Mersing, Johor. The total respondents who responded through face-to-face interviews in June 2014 involving 165 visitors. The data of this study were analyzed using descriptive analysis, gap analysis and Expectation-Perception Analysis (EPA). The results of this study revealed that there are negative gaps between expectation and perception from the visitors’ perspective towards service quality provided by the MPA. Overall, the visitors of the islands were not quite satisfied with the services provided by the MPA. Therefore, the management of MPA needs to improve the quality of their services to attract more visitors visiting the islands.